Treatment Outcome of metastatic lesions from renal cell carcinoma underGoing Extra-cranial stereotactic body radioTHERapy: The together retrospective study. (2020) - Buti, Sebastiano; Bersanelli, Melissa; Viansone, Alessandro; Leonetti, Alessandro; Masini, Cristina; Ratta, Raffaele; Procopio, Giuseppe; Maines, Francesca; Iacovelli, Roberto; Ciccarese, Chiara; Vitale, Maria Giuseppa; De Giorgi, Ugo; et al.
Abstract: Objectives: stereotactic body radiation therapy (SBRT) use has increased overtime for the management of metastatic renal cell carcinoma (mRCC) patients, with a likely good control of irradiated lesions. We planned a retrospective multicenter Italian study, with the aim of investigating the outcome of treatment with SBRT for non-brain secondary lesions in mRCC patients. Methods: all consecutive metastatic non-brain lesions from mRCC that underwent SBRT at nine Italian institutions from January 2015 to June 2017 were considered. The primary endpoint of the study was the lesion-PFS, calculated from SBRT initiation to the local progression of the irradiated lesion. Results: 57 extracranial metastatic lesions from 48 patients with primary mRCC were treated with SBRT. At the median follow-up of 26.4 months, the median lesion-PFS was not reached (43 censored); 72.4% of lesions were progression-free at 40 months, with significantly better lesion-PFS for small metastatic lesions (<14 mm). SBRT was safe and the 1-year local disease control was 87.7%. After SBRT, 18 patients (37.5%) permanently interrupted systemic therapy. Conclusions: consistently with the previous literature, our findings support the use of SBRT in selected mRCC patients.